More than Shelter - Wahab, Kunle Ade (Obafemi Awolowo University Press, 2013)
It is usually conceived, constructed and maintained by man to create within it a micro-environment to satisfy his basic needs. In addition, any building represents a statement of hope for the future. Since it is a response to material and geographical necessities, religious beliefs, social systems and economic conditions, a building is more than mere shelter. Various needs lead to different types of buildings, namely, residential, religious, civic, commercial, industrial, and military, among others.